2015
DOI: 10.1002/2015jc011154
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of the seasonal sea level cycle in the northwest Pacific

Abstract: The seasonal sea level variations observed from tide gauges over 1900–2013 and gridded satellite altimeter product AVISO over 1993–2013 in the northwest Pacific have been explored. The seasonal cycle is able to explain 60–90% of monthly sea level variance in the marginal seas, while it explains less than 20% of variance in the eddy‐rich regions. The maximum annual and semiannual sea level cycles (30 and 6 cm) are observed in the north of the East China Sea and the west of the South China Sea, respectively. AVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
2
33
0
1
Order By: Relevance
“…Interannual to multidecadal variability has been related to changes in atmospheric pressure and wind fields (e.g., Plag and Tsimplis 1999, in the North and Baltic Seas; Marcos and Tsimplis 2007, in Southern Europe; Torres and Tsimplis 2012, in the Caribbean Sea) which, in turn, are linked to climate indices such as NAO. They have also been associated with variability in ocean currents, especially where these are strong (e.g., in the NW Pacific (Feng et al 2015) or western Atlantic (Calafat et al 2018)), or to changes in large-scale forcing patterns in steric height or sea surface temperature (SST) (Wahl et al 2014). The study of Amiruddin et al (2015) made use of both tide gauge and altimeter data from the South China Sea, finding significant differences between the coastal seasonal cycle and that of the nearby deeper ocean.…”
Section: Seasonal Variability In Coastal Sea Levelmentioning
confidence: 99%
“…Interannual to multidecadal variability has been related to changes in atmospheric pressure and wind fields (e.g., Plag and Tsimplis 1999, in the North and Baltic Seas; Marcos and Tsimplis 2007, in Southern Europe; Torres and Tsimplis 2012, in the Caribbean Sea) which, in turn, are linked to climate indices such as NAO. They have also been associated with variability in ocean currents, especially where these are strong (e.g., in the NW Pacific (Feng et al 2015) or western Atlantic (Calafat et al 2018)), or to changes in large-scale forcing patterns in steric height or sea surface temperature (SST) (Wahl et al 2014). The study of Amiruddin et al (2015) made use of both tide gauge and altimeter data from the South China Sea, finding significant differences between the coastal seasonal cycle and that of the nearby deeper ocean.…”
Section: Seasonal Variability In Coastal Sea Levelmentioning
confidence: 99%
“…They suggested that sea surface temperature and sea level pressure are the reason for the amplitude increase. Feng et al [10] indicated that wind forcing and steric component are dominant impacts on the marginal seas and deep ocean (or open ocean) of the northwest Pacific Ocean, respectively. Amiruddin et al [11] also reported similar results in the South China Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Amiruddin et al [11] also reported similar results in the South China Sea. The temporal variation of seasonal sea level cycle has been investigated at regional scales, such as by Wahl et al [2] for the United States Gulf coast, Feng et al [10] and Amiruddin et al [11] for the northwest Pacific coast, Torres and Tsimplis [12] for the Caribbean Sea, and Passaro et al [13] and Cheng et al [14] for the Baltic Sea and North Sea, respectively. Only a few studies have been conducted on seasonal sea level cycle in the Northeast Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this great interest, very few studies have been conducted to investigate the local sea level trend around this deltaic region. Most studies rather focus on a wider scale (e.g., Amiruddin et al, 2015;Feng et al, 2015;Dangendorf et al, 2014;Wei et al, 2010) or on nearby regions (e.g., Luu et al, 2015;Suriyan and Tal, 2014;Sojisuporn et al, 2013). In this study, the inter-decadal and seasonal trends as well as the spatial distribution of the sea level along the Mekong Delta coast were investigated.…”
Section: Introductionmentioning
confidence: 99%